Value chain development for deeper integration of East Asia and Latin America - Benjamin Shepherd (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
This paper uses new data from the Asian Development Bank (ADB) and its partners, including the UN Economic Commission for Latin America and the Caribbean (ECLAC), to track the importance of trade within global value chains in East Asia and Latin America. The analysis shows that while value chain trade is important within the overall trade landscape, it takes place to a significant extent within a traditional paradigm in which Latin America most often supplies raw materials, and East Asia supplies manufactured goods. The pattern is not uniform, but there are important elements of this dynamic at play. While experiences differ significantly across countries and sectors, there is a generally a closer degree of GVC integration between East and South-East Asia than between East Asia and Latin America. Nonetheless, GVC integration between Latin America and South-East Asia in agriculture, mining and service sectors shows promise, with the former supplying inputs used in the latter's export production. Trade costs are likely an important part of the explanation, so further attention to policies like regulatory cooperation in services sectors, as well as trade facilitation, and standards and conformance, would be ways to help promote further integration even in the absence of a comprehensive and broad-based liberalization agreement.
Keywords: F13; F15; O24; 330; International trade; Trade policy; Global value chains; Trade costs; Value added exports; Asia; Latin America